Association of the location of pancreatic ductal adenocarcinoma (head, body, tail) with tumor stage, treatment, and survival: a population-based analysis. (2nd December 2018) - van Erning, Felice N.; Mackay, Tara M.; van der Geest, Lydia G. M.; Groot Koerkamp, B.; van Laarhoven, Hanneke W. M.; Bonsing, Bert A.; Wilmink, Johanna W.; van Santvoort, Hjalmar C.; de Vos-Geelen, Judith; van Eijck, Casper H. J.; Busch, Olivier R.; Lemmens, Valery E.; et al.
Abstract: Background: The association between pancreatic ductal adenocarcinoma (PDAC) location (head, body, tail) and tumor stage, treatment and overall survival (OS) is unclear. Methods: Patients with PDAC diagnosed between 2005 and 2015 were included from the population-based Netherlands Cancer Registry. Patient, tumor and treatment characteristics were compared with the tumor locations. Multivariable logistic and Cox regression analyses were used. Results: Overall, 19, 023 patients were included. PDAC locations were 13, 451 (71%) head, 2429 (13%) body and 3143 (16%) tail. Differences were found regarding metastasized disease (head 42%, body 69%, tail 84%, p  < .001), size (>4 cm: 21%, 40%, 51%, p  < .001) and resection rate (17%, 4%, 7%, p  < .001). For patients without metastases, median OS did not differ between head, body, tail (after resection: 16.8, 15.0, 17.3 months, without resection: 5.2, 6.1, 4.6 months, respectively). For patients with metastases, median OS differed slightly (2.6, 2.4, 1.9 months, respectively, adjusted HR body versus head 1.17 (95%CI 1.10–1.23), tail versus head 1.35 (95%CI 1.29–1.41)). Conclusions: PDAC locations in body and tail are larger, more often metastasized and less often resectable than in the pancreatic head. Whereas survival is similar after resection, survival in metastasized disease is somewhat less for PDAC in the pancreatic body and tail.